A morphological survey of avian Haemosporida in Colombian wild birds: Avian Haemosporida in Colombia - Arroyave Pérez, Arley Onasis; Cifuentes-Rincón, Analorena; Roldán Carvajal, Ingrid Johana; Correa V, Nathalia M (Revista Colombiana de Ciencias Pecuarias, 2024)
Introduction: Infection by protozoan haemoparasites causing malaria in birds is chronic and can lead to physical, reproductive, and behavioral alterations, resulting in a decline in the populations of affected wild birds. Objective: To identify parasitic agents causing avian malaria in a wild bird population in Jardin (Antioquia, Colombia) through blood smears and to explore bird-level factors associated with positivity. Methods: A descriptive cross-sectional study was conducted with non-probabilistic convenience sampling. Blood samples were obtained from wild birds captured with mist nets. Each bird was characterized according to its genus, species, sex, and age group. Three blood smears per bird were prepared and examined for parasitic structures from Haemoproteus, Leucocytozoon, and Plasmodium genera. Descriptive statistics and the association between study variables and the dichotomous outcome of blood smear analysis (positive or negative) using Fisher's exact test. Results: A total of 46 wild birds from 20 different species of the orders Passeriformes and quasi-Passeriformes were captured at six different locations in the study municipality (between 1,665 and 2,053 m.a.s.l.) in July 2022. Structures compatible with Haemosporida causing avian malaria were found, with a general infection frequency of 34.8% (16/46). Among the birds, 32.6% (15/46) were positive for Plasmodium spp., 6.5% (3/46) for Haemoproteus spp., and 4.3% (2/46) for Leucocytozoon spp. In addition, 6.5% (3/46) of the birds were coinfected with 2 or 3 of the agents of interest. An association was found between Plasmodium spp. infection and age group when the bird was defined as an adult (p=0.050). Conclusion: This study contributes to the knowledge of haemoparasites in wild birds in Colombia, reporting the presence of avian malaria in the study area. Further research is required on the molecular identification of protozoan haemoparasites, pathogenicity, the health status of these birds, and the attributable impact on their populations.